Design of Microstrip Antenna Arrays with Rotated Elements Using Wilkinson Power Dividers for 5 G Customer Premise Equipment Applications - Ting-Yi Huang; Yun-Jhang Lee (International Journal of Antennas and Propagation)
Microstrip antenna arrays are proposed in this paper for the customer premise equipment (CPE) applications in the frequency range 1 (FR1) of the 5th generation (5 G) mobile networks. The proposed antenna arrays consist of three FR4 substrates. Antenna elements and feeding networks are optimized separately through parameter studies and then combined to form the proposed antenna arrays. Bandwidth-enhancing parasitic elements on the top substrate are broadside coupled to the microstrip antennas in the middle substrate, which are probe-fed by the microstrip feeding network using Wilkinson power dividers realized in the bottom substrate through the ground plane and the stud supporting air layer between the lower two substrates. Two antenna arrays, with four and eight antenna elements, are proposed for different gain specifications, 10 dBi and 12 dBi, respectively. Bandwidths of 10-dB return loss for both arrays fully covered the 5 G n78 frequency band (3.3–3.8 GHz). 20 dB isolation between antenna elements can also be achieved using the proposed layouts with rotated elements. The dimensions, radiation gain, and efficiency of the proposed antenna units, four-element array, and eight-element array are 65 × 65 × 11.4, 115 × 115 × 11.4, and 115 × 215 × 11.4 mm3, 6.2, 10.5, and 13 dBi, 74%, 56%, and 50%, respectively. The proposed antenna arrays exhibit the advantages of simple, low-cost, low-profile, and high-gain characteristics, which is potentially applicable to 5 G CPE outdoor unit (ODU)-related devices.